2012
DOI: 10.1109/tmi.2011.2181531
|View full text |Cite
|
Sign up to set email alerts
|

Interventional 4-D C-Arm CT Perfusion Imaging Using Interleaved Scanning and Partial Reconstruction Interpolation

Abstract: Abstract-Tissue perfusion measurement during catheterguided stroke treatment in the interventional suite is currently not possible. In this work, we present a novel approach that uses a C-arm angiography system capable of CT-like imaging (C-arm CT) for this purpose. With C-arm CT one reconstructed volume can be obtained every 4-6 s which makes it challenging to measure the flow of an injected contrast bolus. We have developed an interleaved scanning (IS) protocol that uses several scan sequences to increase te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…We considered the perfusion map slices containing the annotated stroke-affected areas inside a sub-volume of size 256 × 256 × 18. To calculate the PC and RMSE, we applied an automated region of interest (ROI) analysis with vascular pixel elimination (VPE) [3]. Therefore, air and vessel structures were excluded from the perfusion maps according to the brain segmentation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We considered the perfusion map slices containing the annotated stroke-affected areas inside a sub-volume of size 256 × 256 × 18. To calculate the PC and RMSE, we applied an automated region of interest (ROI) analysis with vascular pixel elimination (VPE) [3]. Therefore, air and vessel structures were excluded from the perfusion maps according to the brain segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…In [3], first in vivo results of a PCCT study with healthy pigs were presented. A novel approach for PCCT was used, which combines interleaved scanning with partial volume reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies in canines and swine models have now demonstrated the feasibility of dynamic perfusion imaging with the use of a flat detector angiographic system. [10][11][12] The aim of this pilot study was to test the feasibility of this novel application by comparing FD-CTP and FD-CTA with a multimodal MR imaging protocol in patients with acute ischemic stroke. Additionally, the effective patient dose was evaluated.…”
mentioning
confidence: 99%
“…The basic reconstruction represents a modified version of the algorithm reported previously, which uses the widely accepted deconvolution approach to calculate the dynamic perfusion parameters. 11,12 The arterial input function was manually selected at the anterior cerebral artery. We reconstructed all parameters maps (eg, TTP, MTT, CBV, and CBF) by using a 5-mm section thickness and spacing.…”
mentioning
confidence: 99%